The Relationship between Waist-to-Height Ratio and Occurence of Menâs Erectile Dysfunction in Jebres District Surakarta - Renardi, Arga Scorpianus; Hidayati, Rosalia Sri; Murti, Bhisma (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Erectile Dysfunction (ED) in men can be caused by obesity, especially abdominal obesity. Abdominal obesity showed the visceral fat proportion of a man. There are many ways to meassure visceral fat proportion, one of them is Waist-to-Height Ratio (WHtR). The high proportion of visceral fat cause disturbance of blood vessel that may cause ED. This study is aimed to examine the association the occurrence of ED among men with large and small WHtR. Methods: This study was an analytic-observational study with cross sectional approach conducted in Jebres District in September-October 2014. The subjects were 40 men selected using simple random sampling technique. The dependent variable under study was Erectile Dysfunction. The Indepenent variable under study was Waist-to-Height Ratio. The confounding factor to control was age. The data obtained from physical measurements and questionnaire-led interviews with standard questionnaire International Index of Erectile Function (IIEF) for ED diagnostic. The data were analyzed by use of chi-square and multiple logistic-regression, on SPSS 21.0. Results: The result from bivariate analysis showed that 17 out of 20 men with large WHtR (> 0.5) experienced ED (OR = 1.42; p = 0.677); on the other hand, 27 out of 28 men aged > 50 years experienced ED (OR = 27; p = 0.000). Multiple logistic regression analysis showed that men with large WHtR risk experienced ED 1.66 times higher than men with small WHtR. (OR = 1.66; CI = 95% 0.23 to 12.23; p = 0.617). Conclusions: There is association between WHtR and ED. Men with large WHtR risk experiencing ED more than men with small WHtR, this result is not statistically significant. Keyword: Erectile dysfunction, Waist-to-height ratioÂ